2015
DOI: 10.1144/sp414.10
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility and radiometry data used for stratigraphic correlations: case study on Upper Triassic beds in Turkey

Abstract: A Julian/Tuvalian (¼Lower/Upper Carnian) substage boundary within the Kasımlar Formation, recently detected at Aşagiyaylabel (Taurus Mountains, Turkey) by facies analyses and biostratigraphic ammonoid investigations, was additionally detected by magnetic susceptibility (MS) and radiometry data. The Aşagiyaylabel sequence, a key section concerning environmental changes during Early to Late Carnian time, represents a deepening sequence from platform carbonates to pelagic limestones and marls. The Julian/Tuvalian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…† Gamma-ray spectrometry (GRS) measurements are related to the abundance of the three dominant radioactive elements occurring in sedimentary rocks: K, Th and U. For carbonate rocks, K and Th are interpreted as reflecting clastic GRS curves have often been compared with MS patterns, and differences and similarities can provide insight into detrital and/or diagenetic influences (Bábek et al 2010;Koptíková et al 2010a, b, Koptíková 2011Kozłowski & Sobień 2012;Ellwood et al 2013;Grabowski et al 2013;Chadimova et al 2015;Devleeschouwer et al 2015;Mayrhofer & Lukeneder 2015). In Devonian carbonates from the Barrandian area in the Czech Republic (Požáry-3 section), Koptíková et al (2010a) showed that there is a relatively good correlation between MS and GRS (Fig.…”
Section: Comparison With Other Proxiesmentioning
confidence: 99%
See 1 more Smart Citation
“…† Gamma-ray spectrometry (GRS) measurements are related to the abundance of the three dominant radioactive elements occurring in sedimentary rocks: K, Th and U. For carbonate rocks, K and Th are interpreted as reflecting clastic GRS curves have often been compared with MS patterns, and differences and similarities can provide insight into detrital and/or diagenetic influences (Bábek et al 2010;Koptíková et al 2010a, b, Koptíková 2011Kozłowski & Sobień 2012;Ellwood et al 2013;Grabowski et al 2013;Chadimova et al 2015;Devleeschouwer et al 2015;Mayrhofer & Lukeneder 2015). In Devonian carbonates from the Barrandian area in the Czech Republic (Požáry-3 section), Koptíková et al (2010a) showed that there is a relatively good correlation between MS and GRS (Fig.…”
Section: Comparison With Other Proxiesmentioning
confidence: 99%
“…Importantly, these correlations need to be framed in a well-developed biostratigraphic framework. Correlations can then be established through different techniques: † By visual correlation of MS peaks (Crick et al 1997;Geršl & Hladil 2004;Da Silva & Boulvain 2006;Bábek et al 2010;Boulvain et al 2010;Michel et al 2010;Dechamps et al 2015;Grabowski et al 2015;Mayrhofer & Lukeneder 2015;Whalen et al 2015). † The MS curve can also be included in a sequence stratigraphic framework (Whalen & Day 2008, 2010Da Silva et al 2010).…”
Section: Application Of Ms As a Correlation Toolmentioning
confidence: 99%
“…; Lukeneder et al . ; Lukeneder & Lukeneder ; Lukeneder & Mayrhofer ; Mayrhofer & Lukeneder ). During the Carnian, the sediments around Aşağiyaylabel and Yukariyaylabel in the Tarus Mountains were deposited within an intrashelf setting on the western end of the Cimmerian System (Stampfli & Borel ; Lukeneder et al .…”
mentioning
confidence: 99%